A Century-Old Threat: Disseminated Tuberculosis in a Healthy Host – Case Report - Poongodi Santhana Kumarasamy; Bala Ponnuthurai; Stanley James Benjamin Swamidoss; Mohamed Arafath Mohamed (International Journal of Mycobacteriology)
Disseminated tuberculosis (dTB) is usually rare in immunocompetent individuals. We report a case of dTB presented with constitutional symptoms and extensive lymphadenopathy with bilateral lung parenchymal airspace opacities. Histopathological and molecular methods confirmed the etiological agent – Mycobacterium tuberculosis. She was started on first-line antitubercular treatment and she had significant clinical recovery.